Protein isoforms. Origin, structure and functions - Novosylna, O.V. (Вiopolymers and Cell, 2017)
Many proteins in mammalian organism exist as isoforms. These isoforms can be encoded by different genes or produced by alternative splicing of one gene. Despite rapid instrumental progress in the isoform identification, the reasons for their existence and specific functions remain largely unknown. During recent years, attention of researchers was mostly concentrated on spliced isoforms, while the variants of the same protein coded by different genes can play an essential role in different cell processes. This review presents examples of different potential functions of the protein isoforms coded by different genes. Molecular background which could provide a difference between highly homologous protein variants is discussed with an example of isoforms translation elongation factor 1A (eEF1A). Велика кількість білків в організмі ссавців існує у вигляді декількох ізоформ. Ці варіанти кодуються різними гена-ми або є сплайсованими модифікаціями продуктів того ж самого гена. Незважаючи на швидкий інструментальний прогрес у ідентифікації ізоформ, причини їхнього існування та специфічні функції у більшості випадків залишаються достеменно невідомими. Останнім часом увага дослідників здебільшого зосереджена на сплайсованих ізоформах, у той час як різногенні білкові ізоформи можуть відігравати суттєву роль у різних клітинних процесах. У огляді наводяться приклади різних потенційних функцій ізоформ того ж самого білка, які кодуються різними генами. Молекулярне підґрунтя, що може забезпечувати існування такої різниці функцій у високогомологічних білкових ізоформ обговорюється на прикладі останніх досягнень у вивченні ізоформ фактора елонгації трансляції 1A (eEF1A). Многие белки в организме млекопитающих существует в виде нескольких изоформ. Они кодируются разными генами или являются продуктами альтернативного сплайсинга одного и того же гена. Несмотря на быстрый инструментальный прогресс в идентификации изоформ, причины их существования и специфические функции в большинстве случаев остаются точно неизвестными. В последнее время в основном внимание исследователей сосредоточено на сплайсированных изоформах, в то время как разногенные белковые изоформы могут выполнять существенную роль в разных клеточных процессах. В обзоре приводятся примеры разных потенциальных функций изоформ одного и того же белка, кодируемых разными генами. Молекулярные основы существования такой функциональной разницы высокогомологичных белковых изоформ обсуждаются на примере последних достижений в изучении изоформ фактора элонгации трансляции 1A (eEF1A).